PERAN DKPP DALAM PENYELESAIAN PELANGGARAN ETIK PENYELENGGARAAN PEMILU - Zulkarnain, Muhammad; Ningsih, Nanik Prasetyo (JUSTISI, 2023)
The implementation of elections is a fulfillment of the political rights of the people. In order to realize people's sovereignty, a code of ethics for organizing elections was formed which was under the authority of the DKPP. DKPP plays an important role in violations of the implementation of elections in Indonesia, this study aims to analyze the role of DKPP in violations of the implementation of elections. This research is normative legal research. The results of the study show that: The role of the DKPP in the event of a violation will be responsive and responsive to all complaints, as an example can be seen from the two decisions that the author analyzed even though there were results that rejected the complainant's complaint but all of them still went through the problem solving procedure. According to the author, DKPP has carried out its role based on the two decisions above. But regarding the sanctions against the accused, according to the author, it needs to be updated so that it will have a deterrent effect on the accused. Keywords: Settlement of Violations of the Code of Ethics; General Elections; DKPP.